Photogeneration of Organic Free Radicals in Liquid Solutions - Khudyakova, Igor V.; Levin, Peter P. (Mini-Reviews in Organic Chemistry, 2021)
In this brief review, we consider the generation of free radicals by irradiation with UVlight solutions of compounds with weak chemical bonds. Bond Dissociation Energies (BDE) are compared with the energies of photons. Light sources used in industry and academia are listed in this article. Free radicals can be produced by photodissociation and by bimolecular chemical reactions between the electronically- excited state of a molecule and a quencher. Important examples are presented. A special effort is devoted to Light-Emitting Diodes (LED) which gained a wide application in this century. We cited books on free radicals and photochemistry as an introduction, as well as recent publications dated 2020.
Keywords: Excited states